2023
DOI: 10.1080/15592294.2023.2230662
|View full text |Cite
|
Sign up to set email alerts
|

m 6 A mRNA Methylation Analysis Provides Novel Insights into Pigmentation in Sheep Skin

Abstract: N6-methyladenosine (m 6 A) is the most universal post-transcriptional modification of mRNA which may play important roles in verious species. However, the potential roles of m 6 A in the pigmentation of skin are not completely understood. To explore the role of m6A modification in pigmentation of sheep skin, we used MeRIP-seq and RNA-seq to profile the skin transcriptome in black and white coat color ( n= 3). Our results showed that an averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that m 6 A is the most universal post-transcriptional modification of mRNA in various species and plays a key role in growth, reproduction, pigmentation, fat metabolism, nerve development, tumor invasion, immune responses, and other physiological processes by regulating the expression of mRNAs [30,31]. The role of m 6 A methylation of lncRNAs has received much attention from researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that m 6 A is the most universal post-transcriptional modification of mRNA in various species and plays a key role in growth, reproduction, pigmentation, fat metabolism, nerve development, tumor invasion, immune responses, and other physiological processes by regulating the expression of mRNAs [30,31]. The role of m 6 A methylation of lncRNAs has received much attention from researchers.…”
Section: Discussionmentioning
confidence: 99%
“…M 6 A modifications may play important roles in metabolism, growth, development, immune responses, reproduction, and other physiological processes [28][29][30]. We previously identified pigment-associated m 6 A modifications of mRNA in sheep skin [31]. However, the role of lncRNAs m 6 A methylation in sheep skin has not been reported.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 98%
“…The dysregulation of DNA replication (oas03030) may induce melanocyte decay [171]. Transcriptional misregulation in cancer (oas05202) is involved in the regulation of melanin deposition [172]. Glycine, serine, and threonine metabolism (oas00260) may also play a role in the white phenotype [139,143].…”
Section: Go Terms and Pathways Associated With White Woolmentioning
confidence: 99%